The Process: Brexit and the Anatomy of Article 50 - Craig, P (Oxford University Press, 2017)
The chapter offers a holistic legal analysis of the treaty provision regulating withdrawal from the EU. Craig examines Article 50 TEU and maintains that the process of exit from the EU should be divided into three stages, each of which raises major substantive and procedural questions. Stage 1 is the triggering of Article 50 TEU. Stage 2 concerns the withdrawal negotiations, and stage 3 relates to the outcome of the negotiations. As Craig explains, each stage poses specific challenges both for the EU and for the UK, and there are legal questions that have been—and will have to be—answered along the way. According to Craig, however, politics will heavily shape the law, with both the EU and the UK seeking to leverage specific legal argument in support of their preferred bargaining position.